Je „Velký obrat ke krajině" skutečně ekologický? - Hájek, Tomáš (Lidé města, 2001)
We have to take into account, that the BIG TURN TO THE LANDSCPE is the turn to the sustainability, namely the ecological sustainability. The apparent sense to maintain the values of the cultural values stems from the dynamics of spatial relationship between the city and the countryside. We cannot solve the number of relative separated ecological problems (the support of natural agriculture, the support of renewable energy, the sustainability of transportation) without keeping the countryside inhabited, economically alive, ecologically sound as the real background of the city. The ideological stress on the preservation of the values of the cultural landscape is the way, how to make the ecological attitude to renewable energy and natural agriculture convincing. Despite the logical clarity of emphasis on the cultural landscape, there is no unity among the environmentalists with respect to cultural landscape as the ecological topic of highest importance. Some ecologists are afraid, that the apology of the preservation of traditional image of cultural landscape could mouth to the apology of destruction of the rest of wilderness, that is hidden around us within the cultural landscape as well as it could give rise to the new obstacles towards penetrating the spots of wilderness to the cultural landscape. Is that any chance to overcome this - mostly ideological - debate? The emphasis on preservation of cultural landscape does not exlude - for instance - recovery of original nets of biotic systems inside the country. But it is evident, that the intention to regard the old traditional cultural landscape as the only image of cultural lancscape itself worth of protection is the bad way. We have to protect the cultural landscape as the urbanistic space, despite its next look will differ necessarily from its previous shape.